Assessment of pork handlers’ knowledge and hygienic status of pig meat shops of Chitwan district focusing campylobacteriosis risk factors - Ghimire, L; Dhakal, S; Pandeya, YR; Chaulagain, S; Mahato, BR; Satyal, RC; Singh, DK (International Journal of Infection and Microbiology, 2013)
Introduction: Campylobacter causes more cases of diarrhoea than Salmonella and pork is considered as a potential source of Campylobacter infection after poultry. This study aims to assess the butchers’ knowledge and hygienic condition of slaughter slabs and retail pork shops of Chitwan district, Nepal focusing campylobacteriosis risk factors. Materials and Methods: This study was conducted from September-2012 to December-2012. Three sets of semi-structured questionnaires were formed each for slaughter slabs, retail pork shops and pork handlers focusing on butchers’ knowledge and hygienic status of pig meat shops. Each of the workers (n=40) of 10 different pork meat shops were interviewed. Results: Sixty-five percent of the pork handlers were aware about pork borne disease but none of them had heard about campylobacteriosis. Chilling practice was adopted only in 16.7% of the slaughter slabs. None of them had separate dirty section. Only 30% of the pork handlers wore apron regularly. None of them wore gloves and masks and 40% even did not wash hands regularly before and after pork handling. The hygienic practices like sanitation of equipments and regular washing of hands were significantly associated (p<0.05) with level of education. Conclusions: Hygienic condition of pig meat shops of Chitwan is poor which exposes workers as well as meat consumers at risk for campylobacteriosis and other meat borne diseases. Since education was found to affect hygienic practices, awareness generation program focusing pig borne zoonotic diseases seems necessary together with trainings on hygienic meat production and selling techniques. DOI: http://doi.dx.org/10.3126/ijim.v2i1.8004 Int J Infect Microbiol 2013;2(1):17-21